The geological structure of Kastas hill archaeological site, Amphipolis, eastern Macedonia, Greece - Syrides, George; Pavlides, Spyros; Chatzipetros, Alexandros (Bulletin of the Geological Society of Greece, 2017)
This paper presents research results on the geological structure of Kastas hill in Amphipolis, as well as the broader area. They consist of geological and geomorphological observations at Kastas and 133 hills and the surrounding areas, on their geological structure, the stratigraphy and the paleoenvironment. Kastas hill is the site of the largest burial mound discovered in Greece to date. The slopes of its embankment were recorded and modelled in detail using near field photogrammetry. The problem of distinguishing between in situ geological formations and ex situ anthropogenic deposits is also addressed. The bulk volume of Kastas hill consists of natural sediments; these sediments are exposed as successive alternating beds of grayish loose and cohesive sands with scattered pebbles and locally with cobbles. Clayey beds up to ~20-30 cm thick intercalate between the sands. At the top of the hill the anthropogenic deposits are typical of Macedonian tumuli, with soil and clay alternations for sealing and stabilizing them. Paleosoil horizons were observed both in natural sediments and within anthropogenic substrates. Two horizons were sampled for dating by different methods (OSL – optical stimulated luminescence and 14C – Accelerated Mass Spectroscopy). Their dating shows the development of successive deposits during the Iron, Archaic and Classical ages. The AMS dating of a charcoal which is closely associated to the construction of the main monument yielded an age of Cal. BP 2310 = Cal. 360 BC.